20‐Hydroxyecdysone receptor‐activated Bombyx mori CCAAT/enhancer‐binding protein gamma regulates the expression of BmCBP and subsequent histone H3 lysine 27 acetylation in Bo. mori. Issue 2 (6th January 2020) - Lyu, H.; Xu, G.; Chen, P.; Song, Q.; Feng, Q.; Yi, Y.; Zheng, S.
Abstract: Cyclic adenosine monophosphate (cAMP) response element binding protein (CREB)‐binding protein (CBP or CREBBP) plays important roles in regulating gene transcription and animal development. However, the process by which CBP is up‐regulated to impact insect development is unknown. In this study, the regulatory mechanism of Bombyx mori CBP ( BmCBP ) expression induced by 20‐hydroxyecdysone (20E) was investigated. In the Bo. mori cell line, DZNU‐Bm‐12, 20E enhanced BmCBP transcription and histone H3K27 acetylation. BmCBP RNA interference (RNAi) resulted in decreased histone H3K27 acetylation. Additionally, the luciferase activity analysis revealed that the transcription factor, Bo. mori CCAAT/enhancer‐binding protein gamma ( BmC/EBPg ), activated BmCBP transcription, which was suppressed by BmC/EBPg RNAi and promoted by BmC/EBPg overexpression. Electrophoretic mobility shift assay and chromatin immunoprecipitation results demonstrated that BmC/EBPg could bind to the C/EBP cis ‐regulatory elements in two positions of the BmCBP promoter. Moreover, BmC/EBPg transcription was enhanced by the 20E receptor (BmEcR), which bound to the BmC/EBPg promoter. BmEcR RNAi significantly inhibited the transcriptional levels of BmC/EBPg and BmCBP in the presence of 20E. Furthermore, the BmEcR‐BmC/EBPg pathway regulated the acetylation levels of histone H3K27. Altogether, these results indicate that BmEcR enhances the expression of BmC/EBPg, which binds to the BmCBP promoter, activates BmCBP expression and leads to histone H3K27 acetylation. Abstract : BmC/EBPg activated BmCBP transcription by directly binding to BmCBP promoter. 20E receptor (BmEcR) enhanced BmC/EBPg transcription by binding to BmC/EBPg promoter. 20E enhances histone H3K27 acetylation through the cascade activation of BmEcR, BmC/EBPg and BmCBP.